2014
DOI: 10.1016/j.protcy.2014.10.224
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Rateless Secure Network Coding

Abstract: Network coding allows to increase the throughput as well as the robustness of data transmissions. Regarding robustness, especially rateless network coding was shown to be beneficial. However, the vulnerability of mere network coding against attacks requires introducing security mechanisms, and as known, security implies costs. Within this paper, we evaluate the efficiency of secure network coding schemes applied in a rateless manner. Our results show that secure rateless network coding schemes can still outper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A rateless application for evaluating the efficiency of network coding for secure transmissions is proposed in [13]. It was shown that the efficiency parameters need to be matched to the communications requirements to outperform routing.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A rateless application for evaluating the efficiency of network coding for secure transmissions is proposed in [13]. It was shown that the efficiency parameters need to be matched to the communications requirements to outperform routing.…”
Section: Related Workmentioning
confidence: 99%
“…Encryption encodes the messages such that it is unintelligible to an eavesdropper but authorized users can read it correctly [5]. Network coding was proposed by [12] and it allows robustness in data communications [13]. Instead of sending the source packets, linear combinations of packets are transmitted.…”
Section: Introductionmentioning
confidence: 99%